2017
DOI: 10.1007/s11102-017-0839-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative risk factors for postoperative complications in endoscopic pituitary surgery: a systematic review

Abstract: BackgroundThe ability to preoperatively predict postoperative complication risks is valuable for individual counseling and (post)operative planning, e.g. to select low-risk patients eligible for short stay surgery or those with higher risks requiring special attention. These risks however, are not well established in pituitary surgery.MethodsWe conducted a systematic review of associations between preoperative characteristics and postoperative complications of endoscopic transsphenoidal surgery according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
89
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 46 publications
(145 reference statements)
14
89
2
4
Order By: Relevance
“…Lobatto et al 13 also reported that only one out of five series in their review demonstrated an association between tumor size and CSF leaks. [35][36][37][38][39][40] In our cohort of patients, tumor volume was not found to be a significant predictor of CSF leaks or meningitis, although the tumor volume of the patients with CSF leaks trended higher (12.03 AE 12.96 mL) than patients who did not develop a CSF leak (10.7 AE 15.7 mL).…”
Section: Tumor Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lobatto et al 13 also reported that only one out of five series in their review demonstrated an association between tumor size and CSF leaks. [35][36][37][38][39][40] In our cohort of patients, tumor volume was not found to be a significant predictor of CSF leaks or meningitis, although the tumor volume of the patients with CSF leaks trended higher (12.03 AE 12.96 mL) than patients who did not develop a CSF leak (10.7 AE 15.7 mL).…”
Section: Tumor Characteristicsmentioning
confidence: 99%
“…A few studies inconsistently report preoperative risk factors that are associated with postoperative meningitis, such as diabetes mellitus and intraventricular extension of the tumor. [13][14][15] Here, we analyze patients from a single institution undergoing expanded endonasal surgeries for many pathologies, in an effort to identify perioperative factors that may predispose patients to CSF leakage and meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 As discussed by Lobatto et al identifying patients with risk factors for complications like CSF leak is imperative for appropriate consideration of preoperative planning and timing of the operation, patient counseling, consultation or referral to a center of excellence, alternative treatments, and postoperative management such as short versus long stay. 9 Some literature has identified risk factors for postoperative CSF leak. Nishioka et al suggest that prior transsphenoidal surgery and prior radiotherapy to the skull are risk factors, while Dlouhy et al and Ivan et al found that increased body mass index (BMI) was correlated with CSF leak.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Lobatto et al conducted a systematic review on general endoscopic pituitary surgical outcomes and identified 14 studies that examined risk factors for CSF leaks, specifically. 9 Only interventricular extension was consistently associated with CSF leak, although extension was defined in different ways in different studies. Some studies have identified younger age, 13,14 increased BMI, 11,13,14 female gender, 13,14 increased tumor size, 15 and surgeons' learning 16 curve as less consistent associations with CSF leaks.…”
Section: Introductionmentioning
confidence: 99%
“…The most reported postoperative complications of transsphenoidal surgery are postoperative cerebrospinal fluid leak, epistaxis, bleeding, visual deterioration, and meningitis. 2,3 In this article, we reported an unexpected complication of transsphenoidal surgery consisting of an aberrant surgical way through the posterolateral wall of the sphenoidal sinus in place of the posterosuperior wall. Thus, surgeon has removed the petrous apex parts, that is, cochlea, osseous, and membranous labyrinths leading to a right deafness and a facial palsy.…”
mentioning
confidence: 97%